Lipopolysaccharide-Induced Nitric Oxide and Prolyl Oligopeptidase – Inhibitory Activities of Triterpenoids from Sanguisorba officinalis - Ma, Hongyu; Li, Xizhe; Zhang, Yuchen; Chu, Guangsong; Yuan, Zhong (Planta Medica International Open, 2016)
Lipopolysaccharide-induced nitric oxide and the protease prolyl oligopeptidase (EC 3.4.21.26) have been proposed as targets for the treatment of cognitive disturbances such as dementia. In this study, nine triterpenoids isolated from the roots of Sanguisorba officinalis, including arjunic acid (1), rosamultic acid (2), haptadienic acid (3), 1β-hydroxyeuscaphic acid (4), euscaphic acid (5), tormentic acid (6), pomolic acid (7), ursolic acid (8), and oleanolic acid (9), were tested in vitro for their inhibitory activities on lipopolysaccharide-induced nitric oxide in N9 microglia cells and on prolyl oligopeptidase. Among them, 7 exhibited the strongest inhibitory activity on lipopolysaccharide-induced nitric oxide (IC50, 21.9 µM), while 8 and 9 exhibited a significant prolyl oligopeptidase inhibitory activity (IC50 18.1 and 24.0 µM, respectively). The results could provide a clue that these triterpenoids are responsible for the reported neuro-protective effect of S. officinalis.
Keywords: Sanguisorba officinalis; Rosaceae; triterpenoids; lipopolysaccharide-induced nitric oxide; prolyl oligopeptidase